Efektivitas Dakwah Digital dalam Meningkatkan Keberagaman Mahasiswa - Isak Iskandar; Safitri Nur Fadila; Pitaloka Pitaloka; Agung Juansyah (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2024)
In today's digital era, social media, especially Instagram, has become the main platform for spreading information and messages, including da'wah. Students as the young generation who actively use social media have great potential to receive and spread da'wah messages. This study examines the extent to which da'wah delivered through Instagram can influence students' understanding of diversity, both in terms of ethnicity, culture, religion, and other perspectives. The method used is a survey by distributing questionnaires to students from various universities. The results of the study indicate that da'wah on Instagram has a positive influence in increasing students' awareness and understanding of the importance of diversity, as well as encouraging an attitude of tolerance and mutual respect. However, the effectiveness of this da'wah is influenced by the quality of the content, consistency of delivery, and audience involvement. This study concludes that Instagram da'wah can be an effective tool for promoting diversity values ​​among students, with the note that there is an appropriate strategy in delivering da'wah messages